PHYSICS TEACHING TECHNOLOGIES AND DESIGN. (Multidisciplinary Journal of Science and Technology, 2025)
In this article, as a result of the qualification requirements developed in the discipline “Physics Teaching Technologies and Design”, the effective use of active methods of education such as modular, problem-based, and discussion-based, electronic resources, electronic lesson plans, and graphic organizers in organizing lectures, practical, and seminar classes will not only increase the activity of future physics teachers, but also help technical engineers acquire deep, broad theoretical and practical knowledge in this discipline. The leading task of the method is to arouse interest: with the help of purposeful and skillfully posed questions, students are encouraged to remember and express their knowledge on the given topic, discuss it with their classmates under the guidance of the teacher, and together with the teacher, they gradually understand and master new knowledge through independent thinking, conclusion, conclusion, and generalization.